Environmental Communication Policy and Religious Spirituality in Handling Waste Problems in Bintan Regency Riau Islands - Ali Ridho; Mahfuzah Saniah (Talenta Publisher, 2023)
The research discusses the policy of the Regional Government of Bintan Regency in tackling the waste problem through an environmental communication approach and ecology religious spirituality. This research is a case study type and the data is obtained from the observation process and literature study related to the research theme. The results of the study concluded that the environmental communication approach by the Regional Government of Bintan Regency to deal with waste problems must be implemented as soon as possible by involving all components of policy makers, the community, and foreign and domestic private parties. Then, a new approach model is needed in the form of an ecology-based religious spirituality movement to make people aware that religious values also contain teachings about the virtues of protecting the surrounding environment. Religious leaders in collaboration with the local government have more responsibility to provide ecological spirituality content to the peoples